Performance analysis of inertial twist morphing concept in hovering flight - Amoozgar, M.R.; Shaw, A.D.; Zhang, J.; Wang, C.; Friswell, M.I. (My University, 2019)
This paper presents the initial performance analysis of a twist morphing concept based on moving a mass in the chordwise direction in hovering flight. The blade structure is considered to be made of composite materials with bend-twist coupling present in the layup. The chordwise movement of the added mass introduces an additional lag moment along the spar of the blade which is able to change the twist of the blade through the bend-twist coupling. Therefore, the twist of the blade is related to the mass position in the chordwise direction and its magnitude. The blade is modelled by using the geometrically exact fully intrinsic beam equations, and the aerodynamic loads are simulated by using the quasi-steady aerodynamic model combined with uniform inflow. The governing aeroelastic equations are discretized using a time-space scheme. The results show that when the mass moves in the chordwise direction of the blade, the twist distribution of the blade changes. This twist change results in variation of the aerodynamic loads and hence change the aerodynamic performance of the rotor. The results highlighting the importance of the added mass location and magnitude, and the lag-twist coupling value on the reduction in the rotor power required is presented.